PENGARUH IMPLEMENTASI KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KINERJA KARYAWAN - Elly Karmeli; S Suprianto; Abdul Muis; Binar Dwiyanto Pamungkas (Samalewa: Jurnal Riset & Kajian Manajemen, 2021)
This study aims to know the effect the implementation of occupational safety and health (K3) toward employees’ performance in the transmission and distribution sector of Batulanteh Regional water enterprise (PDAM). Type of this study was an associative study which aims to determine the effect or relationship of occupational safety and health (K3) variables as independent variables (X) with employee performance variables as the dependent variable (Y). The data used were quantitative data in the form of respondents' perceptions regarding the object of research collected through questionnaires. Data obtained from the source, namely employees of the transmission and distribution division of PDAM Batulanteh with number of respondents were 20 respondents. Data analyses were used simple linear regression analysis techniques, hypothesis testing and determination coefficient test (R2). Based on the results of data analysis, it was known that t-value of the occupational safety and health (K3) variable toward employees’ performance was 1,945 and the t-table value at the level of ? = 5% was 2,101 (1,945 <2,101). It means that safety and health occupational (K3) variable did not affect the performance of employees in the transmission and distribution sector of PDAM Batulanteh. The ability of safety and health occupation (K3) variables in explaining the variance of changes in employee performance variables in the transmission and distribution sector of PDAM Batulanteh was 12.8%, while the remaining of 87.2% was explained by other variables outside of this study.